PENGEMBANGAN GAME EDUKASI INTERAKTIF BERBANTUAN KAHOOT BERBASIS TEAM GAMES TOURNAMENT TERHADAP KEMAMPUAN PEMECAHAN MASALAH DALAM MATERI LINGKARAN DI MTs MUJAHIDIN PONTIANAK - Sinta Andriyani; Sandie; Yudi Darma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop learning media in the form of interactive educational games assisted by Kahoot integrated with the Team Games Tournament (TGT) learning model to improve mathematical problem-solving skills in the circle material of class VIII students of MTs Mujahidin Pontianak. This study uses the Research and Development (R&D) method with the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were 14 class VIII students. The instruments used included expert validation sheets to assess product validity, teacher and student response questionnaires to measure practicality, and learning outcome tests (posttests) to assess media effectiveness. The results showed that the media developed had a very high level of validity, with an average percentage of 95.23%. The practicality of the media based on the results of the teacher and student response questionnaires reached an average of 82.85%, which was categorized as very practical. Meanwhile, the effectiveness of the media based on the results of the student posttest showed classical learning completion of 86, so it was included in the effective category. Based on these results, it can be concluded that the interactive educational game media assisted by Kahoot based on the Team Games Tournament model is worthy of being used as an alternative learning media that is valid, practical, and effective to improve students' mathematical problem-solving abilities, especially in circle material.